Предмет: Алгебра,
автор: всезнайка53
(x-3)(13-4x-x^2)<(x-3)(x^2+11x-4) Решить неравенство
Ответы
Автор ответа:
0
(х-3)(13-4х-х²)-(х-3)(х²+11х-4)∠0
(х-3)(13-4х-х²-х²-11х+4)∠0
(х-3)(-2х²-15х+17)∠0
(х-3)(-2х²-15х+17)=0
(х-3)=0 х=3
-2х²-15х+17=0
(х-3)(13-4х-х²-х²-11х+4)∠0
(х-3)(-2х²-15х+17)∠0
(х-3)(-2х²-15х+17)=0
(х-3)=0 х=3
-2х²-15х+17=0
Приложения:
![](https://files.topotvet.com/i/734/7349d96446479e79c5df8794cf3d197a.jpg)
Автор ответа:
0
ооо, благодарочка тебе:D
Похожие вопросы
Предмет: Русский язык,
автор: Аноним
Предмет: Английский язык,
автор: Аноним
Предмет: Математика,
автор: alexavanesian
Предмет: Математика,
автор: laska2x
Предмет: Алгебра,
автор: chastowasacha